Apigenin protects against alcohol-induced liver injury in mice by regulating hepatic CYP2E1-mediated oxidative stress and PPARα-mediated lipogenic gene expression. (25th September 2017) - Wang, Feng; Liu, Jin-Cheng; Zhou, Rui-Jun; Zhao, Xi; Liu, Mei; Ye, Hua; Xie, Mei-Lin
Abstract: Alcohol is a major cause of liver injury, and there are currently no ideal pharmacological reagents that can prevent or reverse this disease. Apigenin is one of the most common flavonoids present in numerous plants and has many beneficial effects. But whether or not apigenin may protect against alcohol-induced liver injury remains unknown. Our aim was to examine the effect and potential mechanisms. The experimental mice were given 56% erguotou wine or simultaneously given apigenin 150–300 mg/kg by gavage for 30 days. The results showed that in the apigenin-treated mice, the expression of hepatic cytochrome P450 2E1 (CYP2E1) and nuclear factor kappa B proteins as well as contents of hepatic malondialdehyde and tumor necrosis factor-alpha were reduced, while the levels of hepatic reduced glutathione, glutathione reductase, glutathione peroxidase, and glutathione S-transferase were increased, especially in the 300 mg/kg group. A significant change in hepatic steatosis was also observed in the apigenin 300 mg/kg group. Apigenin pretreatment could increase the expression of hepatic peroxisome proliferator-activated receptor alpha (PPARα) and carnitine palmitoyltransferase-1 proteins, and decrease the expression of hepatic sterol regulatory element binding protein-1c, fatty acid synthase, and diacylglycerol acyltransferase proteins. These findings demonstrated that apigenin might exert a protective effect on alcohol-induced liver injury, and its mechanisms might be related to the regulations of hepatic CYP2E1-mediated oxidative stress and PPARα-mediated lipogenic gene expression. Highlights: Apigenin inhibited alcohol-induced hepatic oxidative stress and steatosis in mice. Apigenin might decrease alcohol-induced hepatic CYP2E1 protein expression. Apigenin might regulate hepatic PPARα-mediated lipogenic gene expression.